Compounds that determine their nutritional value based on the types of food products. - Meliboyev, Mirazam; Qurbanov, Ulug'bek (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
Today, consumers are interested in the general composition of almost all types of manufactured products, and the number of products included in the product is increasing day by day. In this article, the general composition of food products, its energy-giving compounds, biological additives (preservatives, flavoring agents, coloring agents, flavor enhancers), proteins, fats, and carbohydrates are more detailedilluminates.